2015
DOI: 10.1103/physrevc.91.014601
|View full text |Cite
|
Sign up to set email alerts
|

Low-energyR-matrix fits for theLi6(d,α)He

Abstract: Background:The information about the 6 Li(d, α) 4 He reaction rates of astrophysical interest can be obtained by extrapolating direct data to lower energies, or by indirect methods. The indirect Trojan horse method, as well as various R-matrix and polynomial fits to direct data, estimate the electron screening energies much larger than the adiabatic limit. Calculations that include the subthreshold resonance estimate smaller screening energies.Purpose: Obtain the 6 Li(d, α) 4 He reaction R-matrix parameters an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In recent years, THM data allowed for a better understanding of different astrophysical problems, such as the study of light element burning reactions (Pizzone et al 2005(Pizzone et al , 2014Lamia et al 2008Lamia et al , 2012bLamia et al , 2012cLamia et al , 2013Tumino et al 2011aTumino et al , 2011bTumino et al , 2014Grineviciute et al 2015), CNO reactions (see La Cognata et al 2010Sergi et al 2010;Palmerini et al 2013), and removing/producing neutron reactions (Lamia et al 2008;Gulino et al 2010Gulino et al , 2013La Cognata et al 2012). …”
Section: The Thmmentioning
confidence: 99%
“…In recent years, THM data allowed for a better understanding of different astrophysical problems, such as the study of light element burning reactions (Pizzone et al 2005(Pizzone et al , 2014Lamia et al 2008Lamia et al , 2012bLamia et al , 2012cLamia et al , 2013Tumino et al 2011aTumino et al , 2011bTumino et al , 2014Grineviciute et al 2015), CNO reactions (see La Cognata et al 2010Sergi et al 2010;Palmerini et al 2013), and removing/producing neutron reactions (Lamia et al 2008;Gulino et al 2010Gulino et al , 2013La Cognata et al 2012). …”
Section: The Thmmentioning
confidence: 99%
“…The authors of Ref. [10] also showed that this resonance predominantly decays into the αα-channel. They found that the partial width for such a decay is Γ α = 0.77 MeV, which gives Γ α /Γ ≈ 0.96.…”
Section: Fusion Channelsmentioning
confidence: 93%
“…Recent analysis of experimental data, based on the R-matrix parametrization [10], showed that at the near-threshold energies the inelastic collision of d and 6 Li mainly leads to formation of that resonance 8 Be * (2 + , 0, 22.2 MeV). The authors of Ref.…”
Section: Fusion Channelsmentioning
confidence: 99%
“…Besides, the accurate measurement of these reactions in the low energy region may be used to test the nuclear reaction theory that may provide insights into the influence of the Oppenheimer effect [4] and electron screening effect [5] on the cross section at low energies. The analysis of d-T reactions at low energies by R-matrix theory has been proved to be quite successful [6]. This method has been used in deuterium induced reactions on heavier nuclei [7].…”
Section: Introductionmentioning
confidence: 99%